La crise de la sensibilité esthétique : l’art à l’âge virtuel - Sandrine Darsel (Cahiers de Narratologie)
Faced with a crisis of sensitivity to art, the virtualisation of art is presented as a remedy for indifference and incomprehension. Virtual mediation, digitisation of existing works, digital arts... Virtual art is presented as participatory, immersive and interactive. However, an analysis of the ontological and epistemological difficulties associated with the virtualisation of art leads us to rethink a much more general problem, which is the focus of this article: where subjectivism and relativism predominate, sacralising the pleasure of aesthetic experience, we need to discern the cognitive value of art. What are the conditions of art's existence? Is it enough to have a sensitive experience of a work, through virtual immersion, for it to function symbolically? What happens to the work if it is incomplete and vague, as digital interactivity suggests? What happens to the aesthetic properties of the work if they are a matter of feeling and experience? Is the risk of virtualisation not to exacerbate the aesthetic experience and lead to a process of de-semiotisation of art? This is what will be at the heart of the proposed philosophical reflection.